Influence of 805 nm Diode Laser on Plasmid Content of Some Locally Isolated Escherichia coli and Proteus Mirabilis - Abdulsattar, Lubna S.; Jawad, Hussein A.; Al-Jubori, Sawsan S. (Iraqi Journal of Laser, 2010)
This work aimed to investigate the effect of Diode laser 805 nm on plasmid DNA and RNA contents of some Gram negative bacteria represented by Escherichia coli and Proteus mirabilis isolates .Plasmid extraction was done using two methods (Salting out and CTAB method).Different powers and pulse repetition rates for 805 nm Diode Laser were used to study this effect. Results revealed that the plasmid profile of the two species were highly affected using (2, 3) W at different frequencies including 5and 10 kHz as compared with 1 kHz while plasmids were gradually disappeared at 1W, 10 kHz. In the same time the shining of RNA was also decreased gradually then disappeared with increasing powers especially at 2W and 10 kHz causing disappearing of RNA while using 2 W (1, 5) kHz causes gradually disappearing. This may suggests using diode Laser as a successful method in plasmid curing.